Desert kites in Jordan – a new appraisal. (November 2015) - Betts, Alison; Burke, David
<x xml:space="preserve">Abstract</x> The desert kites of Jordan, usually stone‐built enclosures with long trailing walls, are part of a broader phenomenon found throughout specific parts of the Middle East, with similar types of structures known widely across the world. Most commonly, the enclosures are used for trapping large herds of ungulates. Those found in Jordan are more densely packed and of much greater variety than those elsewhere in the Middle East. This paper offers a review of the current state of knowledge concerning desert kites in Jordan, including new data on patterns of orientation and recent studies that help to strengthen the case for a Neolithic date for some of the kite systems.